PENGARUH PENGAWASAN, KOMPENSASI DAN PROMOSI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. SWAKARYA INSAN MANDIRI PEKANBARU - Aprilandi '; Marzolina '; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The study was conducted at PT Swakarya Insan Mandiri in order to determine and analyze the effect of supervision, compensation and promotion simultaneously and partially on the job satisfaction of employees at PT. Swakarya Insan Mandiri (SIM) Pekanbaru. The population is all employees in 2014, which amounted to 60 people. As for taking samples author used census method. The analysis of data using multiple regression. The results showed that the supervision, promotion, and compensation simultaneously have a positive and significant effect on employee job satisfaction, supervision, promotion, partially positive and compensation have a partially positive and significant impact on job satisfaction of employees at PT. Swakarya Insan Mandiri (SIM) Pekanbaru. The suggestion of this research is the company should be able to increase the job satisfaction of employees by increasing employee appreciation to colleagues who support employees in improving their work. Companies should give more attention to provide high motivation, to improve communication by implementing a working system group (team), to provides severe sanctions against employees who do the very fatal violance and to promote employees who excel the higher grade. The company needs to improve its supervision of employees, and must be done directly and timely, also company need to provide timely compensation.Keywords: Monitoring, promotion, compensation, and job satisfaction